Identifikasi dan Pengujian Kualitas Produk Pakan Ikan Lokal di Kalimantan Barat Menuju Produksi Pakan Ikan Berstandar Nasional - Shilman, Idham; Purnamawati, Purnamawati; Susanti, Romi; Irmawan, Fadly (Jurnal Ruaya : Jurnal Penelitian dan Kajian Ilmu Perikanan dan Kelautan, 2025)
In aquaculture businesses, feed is a factor that plays a very important role and determines the success of the cultivation business. Apart from that, feed availability is also a major factor in producing maximum production so that market needs can be met. The feed factor determines production costs reaching 60% - 70%. The method used in this research is field experimentation and laboratory testing. Tests on local feed obtained the following results: ash content 30.44%; water content 9.79%; fat content 6.06%; protein content 38.63%; crude fiber content 3.42%; carbohydrates 11.66%. Meanwhile, the industrial feed test results are as follows: ash content 8.70%; water content 9.80%; fat content 6.19%; protein content 24.84%; crude fiber content 6.76%; carbohydrates 63.71%. From the test results, it can be seen that local feed has a higher composition in terms of ash content and protein content. Meanwhile, industrial feed has a higher value in crude fiber and carbohydrate content. And the water content and fat content have almost the same values for both local feed and industrial feed. Some of the weaknesses in local feed production are the lack of raw materials, unstable production processes and less than optimal packaging processes.